2011
DOI: 10.1021/ie102024u
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Extraction of Glycolic Acid Using Tri-n-Butyl Phosphate and Tri-n-Octylamine in Six Different Diluents: Experimental Data and Theoretical Predictions

Abstract: The present study deals with the equilibrium reactive extraction of glycolic acid from aqueous solution by two different extractants [tri-n-butyl phosphate (TBP) and tri-n-octylamine (TOA)] at constant concentration of 0.573 kmol·m−3 dissolving in a wide range of diluents [n-hexane, decane-1-ol, n-hexane + decane-1-ol (1:1 v/v), 4-methylpentan-2-one (MIBK), benzene, and dichloromethane (DCM)] at isothermal conditions (298 ± 1 K). The effects of various parameters such as acid concentration (0.10−0.57 kmol·m−3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…Potentiometric titration with colorimetry is often used to determine extraction yields in reactive extraction with phenolphthalein as a pH indictor [18,20,21,23,29,34]. However, the usual color turning point of phenolphthalein is at pH=8.2 [46] which means that acidic species at pH > 8.2 are not titrated.…”
Section: Influence Of Toa Impurities On Extraction Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentiometric titration with colorimetry is often used to determine extraction yields in reactive extraction with phenolphthalein as a pH indictor [18,20,21,23,29,34]. However, the usual color turning point of phenolphthalein is at pH=8.2 [46] which means that acidic species at pH > 8.2 are not titrated.…”
Section: Influence Of Toa Impurities On Extraction Performancesmentioning
confidence: 99%
“…In the case of hydrophilic carboxylic acids, these reagents can be hydrophobic basic molecules being able to interact with acidic groups [15]. Among such molecules, long chained aliphatic amines have been widely studied for a large set of carboxylic acids, such as hydroxycarboxylic acids like citric [16][17][18], glycolic [19,20], malic [21,22] and tartaric [23][24][25][26] acids, C3 monocarboxylic acids like acrylic [27], propionic [28][29][30][31] and pyruvic [32][33][34] acids and even lactic acid, an α-hydroxylated C3 monocarboxylic acid (positional isomer of 3-HP) [22,23,35].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyacetic acid (HA, CAS: 79-14-1,Figure 1), the smallest and simplest compound of α-hydroxy acid family [1], is a fundamental organic compound and an important organic synthesis intermediate. HA is widely used in chemical cleaning and daily-used chemical industrial [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Matsumoto M. et al 15À17 and Datta D. 18 reported that positive synergism appears in the extraction of dilute organic acids with trin-octylamine (TOA) by adding TBP as an additive. In our previous work: "Separation of glycolic acid from glycolonitrile hydrolysate by reactive extraction with tri-n-octylamine", 19 result was reported.…”
Section: Introductionmentioning
confidence: 99%